Упростите выражение: [latex](\frac{(x \sqrt{x} -8)}{x-4} - \frac{6 \sqrt{x} }{ \sqrt{x} +2} ):(1- \frac{4}{ \sqrt{x} +2}) [/latex]

Упростите выражение: [latex](\frac{(x \sqrt{x} -8)}{x-4} - \frac{6 \sqrt{x} }{ \sqrt{x} +2} ):(1- \frac{4}{ \sqrt{x} +2}) [/latex]
Гость
Ответ(ы) на вопрос:
Гость
1)(√x-2)(x+2√x+4)/(√x-2)(√x+2)-6√x/(√x+2)=(x+2√x+4)/(√x+2)-6√x)/(√x+2)= =(x+2√x+4-6√x)/(√x+2)=(x-4√x+4)/(√x+2)=(√x-2)²/(√x+2) 2)1-4/(√x+2)=(√x+2-4)/(√x+2)=(√x-2)/(√x+2) 3)(√x-2)²/(√x+2) : (√x-2)/(√x+2)=(√x-2)²/(√x+2)*(√x+2)/(√x-2)=√x-2
Не нашли ответ?
Ответить на вопрос
Похожие вопросы